2019
DOI: 10.3390/su11205560
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Development of Land-Lost Peasants’ Citizenization: A Case Study of Dongbang Town, China

Abstract: Urbanization can be categorized as “spontaneous” and “compulsory” according to its mode of occurrence. In the latter case, the local government acquires the agricultural land and then promotes the transformation of the land-lost peasants to urban residents by enforcing various policy combinations. Based on an empirical case analysis of compulsory urbanization in China, this study proposes that the material assistance and guarantee mechanism provided by the local government is of great significance in the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The ninth paper explores how emerging-market multinational enterprises (EMNEs) from emerging markets are upgrading their operations in their home countries, driven by the transformation of subsidiaries in host counties, which is related to organizational entrepreneur leading culture for open innovation dynamics, in addition to innovation capability [117,118].…”
Section: Organizational Entrepreneurship Leading Culture For Open Innovation Dynamicsmentioning
confidence: 99%
“…The ninth paper explores how emerging-market multinational enterprises (EMNEs) from emerging markets are upgrading their operations in their home countries, driven by the transformation of subsidiaries in host counties, which is related to organizational entrepreneur leading culture for open innovation dynamics, in addition to innovation capability [117,118].…”
Section: Organizational Entrepreneurship Leading Culture For Open Innovation Dynamicsmentioning
confidence: 99%
“…Discussion on promoting a sustainable social integration of passive migrants is more pertinent than criticizing mass resettlement. However, the existing studies focus mainly on the positive impact of formal follow-up support policies on the social integration of PAR migrants [29]. In comparison, this study emphasizes the promoting effect of informal community governance tools, especially CBOs, on the social integration of migrants.…”
Section: Discussionmentioning
confidence: 85%
“…However, passive migrants are frequently the beneficiaries of substantial federal, state, and local support, including affordable housing, healthcare provisions, and skills training opportunities [28]. In the relevant studies, the significance of government assistance has been highlighted, such as the material aid and security mechanisms implemented to facilitate the social integration of migrants [29]. Additionally, passive migrants are often concentrated in urban communities.…”
Section: Literature Review 21 the Four Dimensions Of Social Integrati...mentioning
confidence: 99%
“…In terms of research content, while these studies have demonstrated an implicit link between landlessness and adolescents' human capital, they have not thoroughly examined the impact of landlessness on academic performance indicators that directly reflect individual human capital status and require a careful analysis of the causal mechanisms involved. Land acquisition can be considered the loss of the most important capital for livelihood (Xu et al, 2019;Le and Nguyen, 2020). Limited by resource endowment, land-lost farmers struggle to secure suitable employment in cities, leading to changes in their family's main income patterns.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%